2014
DOI: 10.18632/oncotarget.1609
|View full text |Cite|
|
Sign up to set email alerts
|

Co-targeting the MAPK and PI3K/AKT/mTOR pathways in two genetically engineered mouse models of schwann cell tumors reduces tumor grade and multiplicity

Abstract: Malignant peripheral nerve sheath tumors (MPNSTs) are soft tissue sarcomas that occur spontaneously, or from benign plexiform neurofibromas, in the context of the genetic disorder Neurofibromatosis Type 1 (NF1). The current standard treatment includes surgical resection, high-dose chemotherapy, and/or radiation. To date, most targeted therapies have failed to demonstrate effectiveness against plexiform neurofibromas and MPNSTs. Recently, several studies suggested that the mTOR and MAPK pathways are involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 56 publications
0
63
0
Order By: Relevance
“…mTORC1 activation has also been implicated in MPNST tumorigenesis (33). Although mTORC1 inhibitors have shown some success in NF1 patients (40,41), tumor regression did not occur via the usual mechanisms, with the proangiogenic factor HIF1a remaining elevated under rapamycin treatment (33). Of interest, we also observed that HIF1a protein levels were not completely ablated with rapamycin treatment in all four MPNST cell lines tested.…”
Section: Discussionmentioning
confidence: 71%
“…mTORC1 activation has also been implicated in MPNST tumorigenesis (33). Although mTORC1 inhibitors have shown some success in NF1 patients (40,41), tumor regression did not occur via the usual mechanisms, with the proangiogenic factor HIF1a remaining elevated under rapamycin treatment (33). Of interest, we also observed that HIF1a protein levels were not completely ablated with rapamycin treatment in all four MPNST cell lines tested.…”
Section: Discussionmentioning
confidence: 71%
“…Indeed, the simultaneous activation and intrafamily functional redundancy of Ras proteins in NF1-null MPNST cells suggests that it will be difficult to target these proteins therapeutically. Consequently, some laboratories have asked whether targeting signaling pathways downstream of Ras such as mitogen-activated protein extracellular signal-related kinase (ERK) kinase (MEK) 31,32 and the phosphatidylinositol 3-kinase (PI3K)-Akt-TSC2-mammalian target of rapamycin (mTOR)-S6 kinase 33,34 would be more effective therapeutically. Although initial results indicate that this is the case, note that the full repertoire of Ras-dependent signaling pathways activated in NF1-null peripheral nerve sheath tumors has not yet been defined.…”
Section: Oncogenomics In Mpnst Modelsmentioning
confidence: 99%
“…Interestingly, studies show that inhibiting mTOR activates the Raf/mitogen-activated protein kinase kinase (MEK)/ extracellular signal regulated kinase (ERK) pathway (17)(18)(19). Indeed, dual inhibition of the mTOR and Raf/MEK/ERK signaling pathways is an attractive therapy for malignant tumors (20,21).…”
Section: Introductionmentioning
confidence: 99%